THE “TECHSUCCESS” RATING AND THE FINANCIAL INDICATORS OF HIGH-TECH BUSINESSES: CORRELATION ANALYSIS - A. A. Mikhalchuk; A. V. Hizhnyak; V. V. Spitsin; E. A. Monastyrnyy (Вестник университета)
The authors carry out an analysis of the “TechSuccess” rating and the enterprises’ financial indicators, calculated on the basis of accounting data. The purpose of the paper is to identify the correlations between the stable local ratings of “TechSuccess” and the financial indicators of enterprises. The research method is correlation analysis based on Spearman’s rank correlation. The study has revealed that the local ratings of “TechSuccess”, “Innovative Companies” and “Export Potential” are more stable than the main rating and the rating “Fast-growing Companies”. Enterprises with a higher “Export Potential” rating are characterized by higher growth for the period 2013-2017, as well as lower profitability and financial stability in 2017. Enterprises with a higher innovation rating are  characterized by smaller size and more efficient use of assets. The paper describes the remaining identified  patterns. The results obtained should be taken into account when developing measures to support high-tech  business. In particular, export enterprises have gained advantages during the stagnation period in terms of revenue growth, but lack their own funds for development and are forced to resort to borrowed funds. They need support in this field.